2015
DOI: 10.1093/jrr/rru085
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitizing effect of carboplatin and paclitaxel to carbon-ion beam irradiation in the non-small-cell lung cancer cell line H460

Abstract: The present study investigated the ability of carboplatin and paclitaxel to sensitize human non-small-cell lung cancer (NSCLC) cells to carbon-ion beam irradiation. NSCLC H460 cells treated with carboplatin or paclitaxel were irradiated with X-rays or carbon-ion beams, and radiosensitivity was evaluated by clonogenic survival assay. Cell proliferation was determined by counting the number of viable cells using Trypan blue. Apoptosis and senescence were evaluated by terminal deoxynucleotidyl transferase-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
(41 reference statements)
2
21
0
Order By: Relevance
“…These favorable LC rates may be attributable to a biological advantage of C‐ion RT and a radiosensitizing effect of cisplatin to C‐ion beam irradiation. Recent in vitro studies have demonstrated that the addition of chemotherapeutic drugs to C‐ion RT is a potential method for enhancing its efficacy. Meanwhile, few studies have investigated the radiosensitizing effect of cisplatin to C‐ion beam irradiation in cervical cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…These favorable LC rates may be attributable to a biological advantage of C‐ion RT and a radiosensitizing effect of cisplatin to C‐ion beam irradiation. Recent in vitro studies have demonstrated that the addition of chemotherapeutic drugs to C‐ion RT is a potential method for enhancing its efficacy. Meanwhile, few studies have investigated the radiosensitizing effect of cisplatin to C‐ion beam irradiation in cervical cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 12 C 6þ radiotherapy, as a highly intensive local therapy, has become one of the most used therapeutic strategies for various malignancies. Compared to conventional photon and proton irradiation, 12 C 6þ radiotherapy induces a stronger lethal effect on cancer cells due to the unique physical and biological effects, including superior physical dose distribution (spread-out Bragg peak) [5], smaller volume of irradiated normal tissue [6], higher relative biological effectiveness, lower oxygen enhancement ratio, unrepaired DNA damage and nearly unchanged radio-sensitivity within the cell cycle [7][8][9]. This results in a cell-killing effect that is two to three times greater than that of X-rays [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitors of the enzymes involved in this repair may be candidate radiosensitizers to high‐LET radiation therapy. Ataxia telangiectasia and Rad3‐related (ATR) protein inhibitor VE‐821, activator of ataxia telangiectasia‐mutated (ATM) adenosine monophosphate kinase (AMPK)‐p53/p21 metformin, nonhomologous end‐joining repair inhibitor NU7026, Wee‐1 inhibitor MK‐1775, carboplatin and paclitaxel, HSP90 inhibitor PU‐H71, and mTOR inhibitor rapamycin have been reported to improve the efficacy of carbon ion therapy.…”
Section: Particle Radiotherapy Using Proton and Carbon Ionsmentioning
confidence: 99%
“…Therefore, in order to improve the efficacy of BNCT, it is necessary to develop sensitizers targeting TP53 mutation, DNA repair, and cell cycles, referring to studies of carbon ion beams. These reagents include VE‐821, metformin, NU7026, MK‐1775, carboplatin and paclitaxel, PU‐H71, and rapamycin …”
Section: Boron Neutron Capture Therapymentioning
confidence: 99%